Decolonizing travesti space in Buenos Aires: race, sexuality, and sideways relationality - Di Pietro, Pedro José Javier (Gender, place and culture : a journal of feminist geography, 2016)
Scholars of space usually neglect the history of travesti populations in Latin America. It is misrepresented not only by disciplinary blind spots but also by global narratives concerned with rehabilitating queer subjects within homonormative projects. Analyzing neoliberal narratives that delink conflicts about racialization and sexuality in Argentina, this article makes room to decolonize the study of travesti experience and embodiment in Buenos Aires's red zone. It examines a network of racialized travestis and their spatial practices, including their migration from the Andean northwest to the sex-work circuits of Buenos Aires. Finally, this article introduces the notion of sideways relationality to account for the cultural and spatial labor that racialized travestis perform at the oppositional margins of homonormative reflexivity.